Accelerated wound healing phenotype in Interleukin 12/23 deficient mice - Matias Marie AT; Saunus Jodi M; Ivanovski Saso; Walsh Laurence J; Farah Camile S (BMC, 2011)
Abstract Background The concept that a strong inflammatory response involving the full complement of cytokines and other mediators is critical for unimpaired healing has been challenged by wound healing studies using transgenic and knockout (KO) mice. The present study explored the effect of abrogation of the p40 subunit, which is shared by the pro-inflammatory cytokines interleukin (IL)-12 and IL-23, on wound closure of excisional oral mucosal wounds. Methods Double IL-12 and IL-23 KO mice and C57BL ⁄ 6J wildtype mice were wounded on the dorsal surface of the tongue using a 2 mm biopsy punch. The degree of epithelialization was examined histologically. At specific timepoints wounds were examined for cellular and molecular markers for inflammation and angiogenesis using 1) immunohistochemistry; 2) analysis of RNA expression; and 3) flow cytometric analysis. Results Compared to wild type controls, KO mice displayed enhanced healing, which was driven by a greater influx of neutrophils and macrophages during the early stages of wound healing, and increased induction of messenger RNA (mRNA) for endothelial derived neutrophil attractant (ENA78) chemokine and macrophage inflammatory protein-2 alpha (MIP-2α). Increased mRNA for monocyte-attracting chemokines including monocyte chemoattractant protein (MCP)-1 and MCP-3 was seen from day 1, together with higher levels of IL-1β and IL-6 within 24 hours after wounding. In addition, mRNA for vascular endothelial growth factor (VEGF)-A was upregulated in KO mice within 2 hours after injury, and higher expression of this mediator was confirmed by immunohistochemistry. Conclusion Overall, the accelerated oral mucosal wound healing seen in IL-12/IL-23p40 KO compared to wildtype mice was associated with the early establishment of an inflammatory response and vascularization.